2016
DOI: 10.4102/jamba.v8i2.166
|View full text |Cite
|
Sign up to set email alerts
|

The impact of and responses to flooding in Thulamela Municipality, Limpopo Province, South Africa

Abstract: The frequency of climate-related disasters such as floods is growing due to environmental and human factors. This paper examines the impact of flooding and communities’ perceptions towards responses to flooding in the cases of Maniini and Tshilungwi Villages in the Thulamela Municipality in the Limpopo Province of South Africa. A questionnaire survey was conducted with 60 household respondents in the two selected villages and then analysed. Key-informant interviews with community leaders and municipality offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…The study found that water from mountains came at a higher speed, which caused severe damages to human settlements at the foot of the mountain. These results are similar to the findings by Musyoki, Murungweni and Thifhulufhelwi (2016). In addition, some local communities in Thohoyandou Block F and G, Thohoyandou town and Makwarela Extension 3 were of the view that urbanisation also worsened floods by reducing the permeability of ground surfaces and increasing runoff rates, which is similar to the results found by Parker 1999 cited by Few (2003).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The study found that water from mountains came at a higher speed, which caused severe damages to human settlements at the foot of the mountain. These results are similar to the findings by Musyoki, Murungweni and Thifhulufhelwi (2016). In addition, some local communities in Thohoyandou Block F and G, Thohoyandou town and Makwarela Extension 3 were of the view that urbanisation also worsened floods by reducing the permeability of ground surfaces and increasing runoff rates, which is similar to the results found by Parker 1999 cited by Few (2003).…”
Section: Resultssupporting
confidence: 92%
“…Local communities have also identified allocation of plots for settlement in inadequate areas (such as those in valleys, along rivers and in wetlands) as the main factor causing flood disaster in both rural and urban areas. Similar results have also been found by studies conducted in other areas (Adelekan 2010; Few 2003; Musyoki et al 2016; Sanderson 2000; Smith 1996). In Ndondola and Duthuni villages on the western side of Thohoyandou town, some plots were found to be allocated on valleys and others on flood-prone areas.…”
Section: Resultssupporting
confidence: 88%
“…Given the variability in rainfall combined with poor infrastructure in some parts of VDM, the level of vulnerability increases tremendously. Disaster management by VDM is limited to taking post-disaster measures and implementing few early warning systems (Musyoki, Thifhufhelwi & Murungweni 2016). Thus, identification of hazards (including their trends, probabilities of occurrence and associated risks and vulnerabilities), as has been undertaken in this study, is important.…”
Section: Introductionmentioning
confidence: 99%
“…of life, displaces people and causes flooding [74]. For example, the cultivation on slopes and the clearing of vegetation exacerbated the flooding in the study area as a result of Cyclone Leon-Eline [72].…”
Section: Climate Change and Its Impactsmentioning
confidence: 96%
“…However, despite the decline in overall precipitation, there has been an increase in extreme weather events such as, Cyclone Domonia in 1984 [73], Tropical Storm Irina in 2011-2012 [72] and Cyclone Dineo in 2017 [69]. These cyclones and tropical storms have high-speed winds and precipitate large rain downpours in a short period of time which destroys infrastructure, causes loss of life, displaces people and causes flooding [74]. For example, the cultivation on slopes and the clearing of vegetation exacerbated the flooding in the study area as a result of Cyclone Leon-Eline [72].…”
Section: Climate Change and Its Impactsmentioning
confidence: 99%